Effects of pagtatawas on the quality of beef and pork offals - Mejico, Anna Francheska M. (College of Home Economics, University of the Philippines Diliman, 2013)
This study was done to document existing knowledge and practices of using potassium aluminum sulfate or pagtatawas as an offal cleaning agent among selected processors and consumers; and to determine the effects of said treatment to the physicochemical, microbial, and sensory properties of beef and pork offal. A generic pagtatawas protocol for offal was established from the results of documentation, and applied to beef and pork offal. A significant decrease in color lightness and chroma values were observed from the treated offal samples. Th pagtatawas treatment reduced the TPC, TCC, and generic E. coli on the treated samples. Salmonella was not detected in the treated and untreated offal samples. Gross histological observation from sections of offal revealed general constriction of tissue post-tawas treatment. Sensory evaluation of the treated and untreated samples showed significant differences in color, odor, and overall quality in pork offal samples but not in beef offal samples as detected by triangle tests. The results of this study may serve as baseline information in the future establishment of standards for the safe use of tawas treatments for offal.